Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bbapap.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The prosegment catalyzes native folding of Plasmodium falciparum plasmepsin II

Abstract: Plasmepsin II is a malarial pepsin-like aspartic protease produced as a zymogen containing an N-terminal prosegment domain that is removed during activation. Despite structural similarities between active plasmepsin II and pepsin, their prosegments adopt different conformations in the respective zymogens. In contrast to pepsinogen, the proplasmepsin II prosegment is 80 residues longer, contains a transmembrane region and is non-essential for recombinant expression in an active form, thus calling into question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Last, abnormal phi values (i.e., a rare result when the ratio ΔΔ G ‡ /ΔΔ G N‐U upon mutation of an amino acid residue does not fall between zero and one) have been implicated in frustrated regions of well‐studied protein models such as chymotrypsin inhibitor 2 (CI2) or the SH3 domain 9,13 . Although observations of memory effects, severe kinetic trapping, abnormal phi values, and a lack of folding cooperativity have been reported in mature protease folding, their connection to un‐evolved folding landscapes has not been extensively examined until now 6,7,30,43,44 …”
Section: The Mature Protease Is Not Required To Fold (And Can Behave ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Last, abnormal phi values (i.e., a rare result when the ratio ΔΔ G ‡ /ΔΔ G N‐U upon mutation of an amino acid residue does not fall between zero and one) have been implicated in frustrated regions of well‐studied protein models such as chymotrypsin inhibitor 2 (CI2) or the SH3 domain 9,13 . Although observations of memory effects, severe kinetic trapping, abnormal phi values, and a lack of folding cooperativity have been reported in mature protease folding, their connection to un‐evolved folding landscapes has not been extensively examined until now 6,7,30,43,44 …”
Section: The Mature Protease Is Not Required To Fold (And Can Behave ...mentioning
confidence: 99%
“…Clearly, an important selection pressure on PS evolution is the spatiotemporal regulation of proteolysis, as uncontrolled proteolysis can lead to several diseases 47 . Modulation of protein folding landscapes is another likely evolutionary pressure on PS evolution in some proteins and will be the focus of the discussion in this article 4,7,43,44 . Last, the evolution of the zymogen sequence is of course closely connected to its mature sequence, which cannot evolve in such a way that prevents PS folding and must allow for enzyme catalysis and its associated dynamical motions around the native energy basin 48 …”
Section: Evolution Of the Prosegmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have shown that the truncated prosegment assists in correct folding of pro‐tPMII, with a mechanism similar to that of pepsin [16]. Crystal structures of pro‐tPMs have been determined for P. falciparum PMII (pro‐tPMII) [17,18], HAP (pro‐tHAP) [19], PMIV (pro‐tPMIV) [18], and P. vivax PM ( Pv ‐pro‐tPM) [20].…”
Section: Introductionmentioning
confidence: 99%